Energy balance and macronutrient intake during season trainings: influence on anthropometric and lipid profiles in professional athletes - Gowdak, Marcia Godoy (2017)
This study evaluated energetic balance and macronutrient intake at competitive training and transition training and their impact on anthropometric and lipid profiles in sixteen professional male athletes. Dietary data, body composition measurements and lipid profile were obtained at the end of both season trainings. Despite increased carbohydrate supplementation during exercise and higher caloric intake at competitive training (+10%, P =0.01), total daily energy expenditure was higher than caloric intake (79%, P<0.001). These results show negative energy balance at competitive training. However, total daily energy expenditure and caloric intake were similar at transition training (P =0.35). Higher intake of carbohydrate, fat, and protein were observed at competitive training (+13%, P =0.001 for all), although caloric intake was below the requirements during this period. Body mass (+2%, P =0.05), body fat percentage (+56%, P =0.01), fat mass (+57%, P =0.01), and waist and hip circumferences (+10%, P =0.004) were higher at transition training, as well as total and LDL-cholesterols (+14%, P =0.001). Endurance athletes showed negative energy balance at competitive training and maintained similar caloric intake at transition training despite decreased total daily energy expenditure, which might have contributed to changes in anthropometric and lipid profiles. These findings emphasize the importance of nutritional counseling for professional athletes during different season trainings.